Governance beyond the nation-state: Transnationalization and europeanization of the Baltic Sea Region - Kristine Kern; Tina Löffelsend (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
After the end of the Cold War, the Baltic Sea Region (BSR) developed into a highly dynamic area of cross-border cooperation and transnational networking. Four types of governance beyond the nation-state are discussed here: (1) international regimes, such as the Helsinki Convention for the Protection of the Baltic Sea; (2) transnational policy networks, such as Baltic 21, the world's first regional Agenda 21; (3) transnational networks, such as the Union of the Baltic Cities (UBC); and (4) the European Union with approaches such as the “Northern Dimension” for the development of the Baltic Sea Region. Governance towards sustainable development of the Baltic Sea Region undoubtedly requires a combination of national governance with these governance types beyond the nation-state. In this respect, transnational (policy) networks and the European Union provide promising new approaches that can complement the traditional forms of international and intergovernmental cooperation between nation-states. These new governance types represent two parallel trends: a development towards (1) transnationalization and (2) the Europeanization of the Baltic Sea Region. – – Nach dem Ende des Kalten Krieges entwickelte sich die Ostseeregion zu einem außerordentlich dynamischen Raum der grenzüberschreitenden Kooperation und der transnationalen Netzwerkbildung. In dem vorliegenden Artikel werden vier Typen der Governance jenseits des Nationalstaates diskutiert: (1) internationale Regime wie die Helsinki-Konvention zum Schutz der Ostsee; (2) transnationale Politiknetzwerke wie die Baltic 21, die weltweit erste regionale Agenda 21; (3) transnationale Netzwerke wie die ,,Union of the Baltic Cities“ (UBC); und (4) die Europäische Union mit Ansätzen wie der ,,Northern Dimension“ zur Entwicklung der Ostseeregion. Governance in Richtung auf eine nachhaltige Entwicklung des Osteseeraums erfordert zweifelsohne eine Kombination aus nationaler Governance mit diesen Governance-Typen jenseits des Nationalstaats. In dieser Hinsicht liefern transnationale (Politik-)Netzwerke und die Europäische Union viel versprechende neue Ansätze, welche die traditionellen Formen der internationalen und intergouvernementalen Kooperation zwischen Nationalstaaten ergänzen können. Diese neuen Governance-Typen repräsentieren zwei parallele Trends in Richtung auf (1) die Transnationalisierung und (2) die Europäisierung der Ostseeregion.
Keywords: 300